Self-activating anti-infection implant - Jieni Fu (Nature Portfolio, 2021)
Bone implants with antibacterial and osteogenic properties are important for clinical applications, but creating both properties simultaneously remains challenging. Here, the authors demonstrate a self-activating implant using a hydroxyapatite and molybdenum disulfide coating which accelerates bone regeneration and at the same time prevents bacterial infection.